Design of a Sensitive Electrochemical Sensor Based on Ferrocene‐reduced Graphene Oxide/Mn‐spinel for Hydrazine Detection. Issue 2 (5th October 2020) - Singh, Manorama; Bhardiya, Smita R.; Asati, Ambika; Sheshma, Harendra; Rai, Ankita; Rai, Vijai K.
Abstract: Herein, we report construction of a ferrocene‐reduced graphene oxide‐Mn spinel modified glassy carbon electrode (Fc−G/Mn3 O4 /GCE) as a sensitive electrochemical probe for hydrazine detection via its oxidation. The synergistic effect of ferrocene, graphene oxide and Mn3 O4 provides it a great electrocatalytic effect. The electrochemical investigations of Fc−G/Mn3 O4 /GCE were studied using cyclic voltammetry, while differential pulse voltammetry was utilized for recording the electrocatalytic sensing of hydrazine. The prepared Fc−G/Mn3 O4 offers a platform for sensitive and selective detection of low‐level hydrazine in two linear ranges from 0.045 to 108 μM and 108 to 653 μM with limit of detection 8.5 nM. Real sample analysis was also performed in local industrial water samples with satisfactory recovery results. Abstract :